Structure and luminescence properties of multicolor phosphor Ba2La3(GeO4)3F:Tb3+, Eu3+. Issue 61 (4th November 2019) - Ma, Xiaoxue; Liao, Libing; Guo, Qingfeng; Liu, Haikun; Yang, Dan; Liu, Ning; Mei, Lefu
Abstract : Single-phase Ba2 La3 (GeO4 )3 F:Tb 3+, Eu 3+ phosphors were obtained for the first time. Abstract : A new kind of multicolor phosphor Ba2 La3 (GeO4 )3 F:0.15Tb 3+, x Eu 3+ (BLGOF:0.15Tb 3+, x Eu 3+ ) has been acquired through the traditional high temperature solid phase synthesis method. The structural information of the phosphor was studied by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Rietveld refinement. The optical properties of the phosphor have also been studied in detail, including its photoluminescence spectra (PL), photoluminescence excitation spectra (PLE), fluorescence decay curves, energy transfer mechanism and thermal quenching spectra. It has been found that the optimum concentration of Eu 3+ in BLGOF:0.15Tb 3+, x Eu 3+ is 0.24 mol and the energy transfer mechanism from Tb 3+ to Eu 3+ in BLGOF is quadrupole–quadrupole. The color of BLGOF:0.15Tb 3+, x Eu 3+ phosphors can be changed from green to yellow/orange to red. Some details of the energy transfer are reviewed and the effect of complex anion regulation on thermal stability has also been studied. All the properties are good and can contribute to the promotion from the laboratory to practical application for the phosphor.